Dostoevsky's Protagonists as an Embodiment of Nineteenth Century Russia: A New Historicist Reading - M. Balakrishnan, M. B. Usha (2002)
New Historicism is applied in this examination of Dostoevsky's selected protagonists, the Underground Man and Raskolnikov. The protagonists' discourse and polemics are examined in relation to the cultural, political, social, economic and historical context of the 1860 Russia. The analysis shows an emerging pattern of a new social and economic order that alienates, displaces and subjugates the youth of the era. The Underground Man's monologue and Raskolnikov's actions and psychological tunnoil suggest an oppressive hand in the political and social system. It also highlights the beginnings of radicalism as a result of the existing suppression. The dissonance in the protagonists' multi-layered polemics is examined as the mediated discourse, which implies domination, inequality among the working class and a perpetuation of class distinction. The discrimination causes dissatisfaction and marginalization among the underprivileged The progressive ideas of the time encourage action that is directed by reason and rationalism. Indirectly the rationalistic ideas become an excuse for the privileged to further dominate over these protagonists, which intensifies their alienation. The protagonists' arguments and actions imply that the socialist ideology does not eradicate inequality. Contrarily, they accentuate the characters' displacement in the society. Furthermore, the innate corruptness of man is hinted as the reason for the failure of this utopianism. Dostoevsky's characterization is perhaps an attack on the degeneration of man and the values of the milieu. The analysis reflects a deep sense of loss and disillusionment in the protagonists in a materialistic society. The protagonists' discourse could be the voice of the intelligentsia or the nihilists of the era that reflects their alienation in a society where the reforms they believed would change the social order did not materialize.